Piano Sonata no. 8 in C minor, op. 13, published by André - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Offenbach am Main; Germany; Johann André, 2024)
Piano Sonata no. 8 in C minor op. 13, published by J. André in the Sonates pour Pianoforte, from André's Oeuvres de L. van Beethoven pour le pianoforté seul & à quatre mains, originally published between 1804-1838. With additional imprint on Ewer & Co. at 72, Newgate St.